The prediction of fatigue life of asphalt mixtures using four-point bending tests - Pais, Jorge C. (2010)
Fatigue resistance is used in the analysis and design of pavements to predict their life cycle. The results of fatigue tests are expressed in terms of the number of cycles for the tensile strain level applied. Two constants (k1 and k2) take part in this relationship. To know these two constants, at least two fatigue tests are needed, performed at different strain levels to obtain those constants. However, based on laboratory results analysis, k1 and k2 can be correlated and, in this case, the relationship between the fatigue life and the strain level has only one constant, which can be evaluated using the results obtained by a fatigue test. This paper presents the evaluation of the k1 and k2 relationship for Portuguese mixtures based on the results obtained from more than 50 different asphalt mixtures and the prediction of only one of those constants with fatigue test results. The paper also presents an analysis of the fatigue life using fatigue laws with only one constant.